Person-centre care for dementia patients (backend system) - Wu, Zhen Hui (2018)
Dementia is a mental health condition that primarily affects older people and is caused by damage to the brain cells that would affect brain functionality, reducing one’s ability to perform. Caregivers and their guardians frequently experience high levels of stress and anxiety, and it can be overwhelming to take care of a loved one with dementia. With the increasing number of dementia patients, there is a greater demand for healthcare facilities and caregivers. To support the needs of a dementia patient and their caregiver, a group of university final year students have developed an online centralized platform system.